Gold (I/III)‐Catalyzed Trifluoromethylthiolation and Trifluoromethylselenolation of Organohalides. (3rd February 2022) - Mudshinge, Sagar R.; Yang, Yuhao; Xu, Bo; Hammond, Gerald B.; Lu, Zhichao
Abstract: The first C−SCF3 /SeCF3 cross‐coupling reactions using gold redox catalysis [(MeDalphos)AuCl], AgSCF3 or Me4 NSeCF3, and organohalides as substrates are reported. The new methodology enables a one‐stop shop synthesis of aryl/alkenyl/alkynyl trifluoromethylthio‐ and selenoethers with a broad substrate scope (>60 examples with up to 97 % isolated yield). The method is scalable, and its robustness is evidenced by the late‐stage functionalization of various bioactive molecules, which makes this reaction an attractive alternative in the synthesis of trifluoromethylthio‐ and selenoethers for pharmaceutical and agrochemical research and development. Abstract : The first gold(I/III)‐catalyzed direct trifluoromethylthiolation and trifluoromethylselenolation of organohalides are reported. This mild and efficient protocol enjoys a broad substrate scope and high yield (>60 examples with up to 97 % isolated yield). Its robustness was demonstrated by the late‐stage functionalization of various bioactive molecules, which makes this reaction applicable to pharmaceutical and agrochemical research and development.